Implementasi Layanan Payment Gateway pada Sistem Informasi Travel Haji dan Umroh - Fikri, Nidhal; Saputra, Eki; Syaifullah, Syaifullah; Fronita, Mona; Marsal, Arif (Program Studi Teknik Informatika Universitas Pamulang, 2024)
PT Hajar Aswad Mubaroq Riau is a company that offers Hajj and Umrah travel services. However, currently they still use conventional methods in conducting their travel business processes as a whole. So that to improve the efficiency and performance of the travel company's business, it is necessary to implement an information system. In addition, the presence of information systems is expected to significantly reduce administrative costs and increase customer convenience in the transaction process. Before developing an information system, observations are made first to find out which business processes can be implemented in an information system. Information system development uses a Rapid Application Development approach that focuses on rapid development in a short time. The integration of the midtrans payment gateway into the information system has made it easier for researchers to develop a system that supports transaction payments through several banks and e-wallets in Indonesia.